THE TRIASSIC/JURASSIC BOUNDARY IN THE ANDES OF ARGENTINA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
The Arroyo Malo Formation at Alumbre Creek, on the northern bank of the Atuel River, west central Argentina, comprises a c. 300 m thick continuous marine succession across the Triassic-Jurassic System boundary, consisting of massive and laminated pelites indicative of a slope depositional environment. Late Triassic invertebrates, including ammonoids, nautiloids, bivalves, gastropods, brachiopods and corals are restricted to the lower 150 m. Beds between 125-135 m from the bottom yield Choristoceras cf. marshi Hauer, a species found in the Marshi/Crickmayi Zone of Europe and North America, together with loose fragments of Psiloceras cf. pressum Hillebrandt, coeval with the lower to middle part of the Hettangian Planorbis Zone. About 80 m higher are beds yielding Psiloceras cf. rectocostatum Hillebrandt, a species that gives name to an Andean biozone partially coeval with the Johnstoni and Plicatulum Subzones, upper Planorbis Zone. Other fossils recorded in the Rhaetian strata of this section are foraminifers, ostracods and plant remains identified as Zuberia cf. zuberi (Szaj.) Freng. and Clathropteris sp. The section was also sampled for conodonts and radiolarians, thus far with negative results. A palaeomagnetic study is underway.